Telaah Terhadap Alasan Memperingan Sanksi Pidana Dalam Putusan Mahkamah Agung Nomor 813/K/PID/2023 - Silviana Putri, Szyva; Adhari, Ade (LPPM Universitas Ekasakti Padang, 2024)
Considering Indonesia is a nation of laws, as stated in Article 1 paragraph (3) of the Constitution of 1945, the rule of law, not man, should govern the state. But when we examine this issue, we find that an authority figure who is meant to lead by example and safeguard the public is still negligent and has an insufficient comprehension of the law. A senior police officer can nevertheless be included in the